Inhibitory potential of probiotic strains against pathogens associated with osteomyelitis of the jaws: a quantitative MIC and MBC analysis: Curative role of probiotics in jaw osteomyelitis - Baazeem, Moayad; Niazy, Abdurahman; Rabea, Sameh; Alomiery, Abdulaziz A. (Cellular and Molecular Biology, 2025)
Osteomyelitis of the jaw is a significant health burden, often associated with biofilm formation, antimicrobial resistance, and complex bacterial interactions. This study aimed to evaluate the antibacterial efficacy of two probiotic strains, Lactobacillus reuteri DSM 17938 and ATCC PTA 6475, against three key pathogens: Fusobacterium nucleatum, Actinomyces israelii, and Staphylococcus aureus. The focus was on their potential as adjunctive treatments for osteomyelitis of the jaws. This in-vitro study employed tailored standard protocols to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the probiotic strains against the tested pathogens. Probiotic suspensions were prepared in serial dilutions and bacterial strains were inoculated into brain heart infusion media for exposure. The growth inhibition and eradication were confirmed through subculture techniques and microscopic examination of Gram-stained samples. Both probiotic strains exhibited significant antibacterial activity against Fusobacterium nucleatum and Actinomyces israelii at low concentrations, achieving MIC of 0.625 µl and MBC of 1.25 µl for both pathogens. In contrast, Staphylococcus aureus demonstrated greater resistance, with MIC and MBC recorded at 100 µl and 200 µl, respectively. The differential response underscores the variable susceptibility of bacterial species to probiotics and highlights the potential for selective therapeutic application. Within the scope of this study, two Lactobacillus reuteri strains demonstrated promising antibacterial effects against Fusobacterium nucleatum and Actinomyces israelii, suggesting their potential utility in managing osteomyelitis of the jaws. However, higher concentrations or synergistic approaches may be needed to combat Staphylococcus aureus. Further studies including preclinical and clinical trials are essential to translate these findings into effective therapeutic strategies.